An Application of Declarative Languages in Distributed Architectures: ASP and DALI Microservices. - Costantini, Stefania; De Gasperis, Giovanni; De Lauretis, Lorenzo (International Journal of Interactive Multimedia and Artificial Intelligence, 2021)
In this paper we introduce an approach to the possible adoption of Answer Set Programming (ASP) for the definition of microservices, which are a successful abstraction for designing distributed applications as suites of independently deployable interacting components. Such ASP-based components might be employed in distributed architectures related to Cloud Computing or to the Internet of Things (IoT), where the ASP microservices might be usefully coordinated with intelligent logic-based agents. We develop a case study where we consider ASP microservices in synergy with agents defined in DALI, a well-known logic-based agent-oriented programming language developed by our research group.